2009
DOI: 10.1007/s11062-009-9080-5
|View full text |Cite
|
Sign up to set email alerts
|

Interrelations between Peculiarities of the Motivational Sphere of a Personality and Characteristics of the Current EEG

Abstract: In a group of 70 adult subjects of both sexes, we estimated the levels of the need for achievement and its motivation (interpreted as generalized characteristics of the state of the motivational sphere of a personality and diagnosed using questionnaires of Orlov and Mehrabian) and examined the correlations of these estimates with spectral powers (SPs) of the frequency components (rhythms) of the current background EEG (С3 and С4 leads according to the 10-20 system). Despite the fact that naturally high interin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
(11 reference statements)
1
5
0
Order By: Relevance
“…Other researchers consider desynchronization of the θ rhythm in the frontal and parietal regions (similar to that of the α rhythm) in the course of resolving imagery/spatial tasks as related to the necessity of fixation of information in short-term memory [13]. In our tests, we noticed higher powers of the θ rhythm in more motivated and socially adapted subjects [14,15]. Taking this into account, we conclude that internals are, in general, more socially adaptive; they have a higher level of neural/mental stability, a wellmanifested communicative potential, and significant motivation for achievements.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Other researchers consider desynchronization of the θ rhythm in the frontal and parietal regions (similar to that of the α rhythm) in the course of resolving imagery/spatial tasks as related to the necessity of fixation of information in short-term memory [13]. In our tests, we noticed higher powers of the θ rhythm in more motivated and socially adapted subjects [14,15]. Taking this into account, we conclude that internals are, in general, more socially adaptive; they have a higher level of neural/mental stability, a wellmanifested communicative potential, and significant motivation for achievements.…”
Section: Discussionsupporting
confidence: 67%
“…Other researchers observed relatively low powers of θ and α oscillations in individuals of a "mental" type (according to the Keirsey questionnaire), while these powers were greater in persons whith dominating functions of sensation [17]. Our earlier studies demonstrated that absolute and normalized SPs of the α rhythm are, in general, greater in motivated and welladaptable subjects [14,15]. Mosyagin found intense direct correlations of the α rhythm amplitude in the occipital leads with the level of general internality and estimates in the "field of achievements" [3].…”
Section: Discussionmentioning
confidence: 62%
“…In our previous paper [3], we described in detail our sampling from the aspect of psychological indices of the tested subjects. The means of the amplitudes of the ERP components recorded in our study are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The subjects were divided into subgroups with different N-Ach and AchM levels according to the results of interviewing, similarly to how it was made in our preceding work [3].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation